The Effect of Product Variants, Service Levels and Price Bundling on Customer Loyalty - Hanafia, Fifi; Permadi, Hanif Nanda (Lentera Ilmu Nusantara, 2023)
The development of the business world is currently experiencing a very rapid increase, one of which is the food and beverage business. It is proven by the increasing number of new businessmen who have entered the market with various strategies used to attract as many consumers as possible. Companies are not only trying to attract new and many consumers, therefore companies are trying hard to retain the customers they have got. The business of beverage and food companies is currently booming offering various kinds of food/beverage products that are offered with a variety of new innovations that are able to win the hearts of consumers and are no doubt able to compete in the market, because the Indonesian people themselves are basically the majority of food enthusiasts. and drinks. This study aims to determine whether product variants, service levels and price bundling affect customer loyalty at PT Satria Buana Sakti. The type of research used is quantitative. With a population of 150 and sampling with non-probability sampling technique with a sample of 55 respondents. Data collection includes observation and distributing questionnaires. The analytical methods used are validity test, reliability test, classical assumption test, multiple linear regression analysis and hypothesis testing. From the results of the research, the multiple linear regression equation is Y = 1.603 + 0.042 X1 + 0.178 X2 + 0.529 X3. From the analysis of the coefficient of determination, it can be explained that the product variance, service level and price bundling are 67.6%, while the remaining 32.4% is influenced by other variables.